Guidance and Counseling through Fish and Vegetable Cultivation Innovation in Bucket (Budiksamber)Use Regional Economic Empowerment in Cipedes District, Tasikmalaya City - Hisam Ahyani; Agus Setiana; Dodo Suhada; Agus Yosep Abduloh (Farmers: Journal of Community Services, 2021)
The need for food is something that plays a very important role for the community, especially in the midst of a pandemic like now. Budiksamber as one of the programs launched by the Tasikmalaya City Food Security Care community in collaboration with the Syahla Community can be an alternative to meet food needs, especially those whose income is directly affected by the presence of Covid-19. Innovations made in overcoming the economy in the midst of the COVID-19 pandemic, namely through empowering the use of land around the house, which with the presence of the Budiksamber Program as a form of Economic Empowerment for the Bingluh Group in Cipedes District, Tasikmalaya City, is here to provide solutions in overcoming community denominations, the benefits of the Budiksamber program In addition to gaining knowledge and experience in the management of fish and vegetable cultivation in buckets, it can also economically help reduce the risk of kitchen costs.